Could long-term overhead load in painters be associated with rotator cuff lesions?: A pilot study - Loew, Markus; Doustdar, Sepehr; Weber, Marc-André; Bruckner, Thomas; Porschke, Felix; Raiss, Patric; Schiltenwolf, Marcus; Al Mansour, Haidara; Akbar, Michael (PLOS ONE, 2019)
Background Use of the arm above shoulder level has been described as a risk factor for developing rotator cuff tears (RCT). There is a lack of information regarding the frequency and distribution of RCT in a population using their arms above shoulder level during daily work. The aim of this study was to analyze clinical and radiographic findings in a population of painters working more than 10 years and to compare the results with a control group (CG) Materials and methods 100 individuals working more than 10 years as a painter were compared to 100 matched controls without using their arms above shoulder level. MRI scans were performed in all participants. Clinically, the Constant score, DASH score and range of motion (ROM) of the shoulders were analyzed. Results In the painter group (PG) a tear of the supraspinatus tendon was detected in 45% (10%full-thickness; 35% partial) compared to 8% in the (CG) (3% full-thickness; 5%partial; p<0.001). Impingement test was painful in 52% of PG and 7% of CG (p<0.001). The Constant score in the PG was significantly lower compared to the CG (62 vs. 93 points; p<0.001). PG had significantly worse DASH scores and inferior active and passive ROM of the dominant shoulders. In the multivariable logistic regression analysis, three risk factors (smoking, sports activity, and handedness) showed no effect. However, group membership (PG/CG) and age revealed a significant effect. Conclusion Long-term occupational load on the shoulders in painters seems to be associated with an increased risk for developing RCT. Our findings may provide support for developing preventive strategies for this unique cohort. Level of evidence: III